Direction of teaching in nursing towards the management of care in the SUS: compatibility between training and the product (Research, Society and Development, 2023)
Introduction: The creation of the Unified Health System (SUS) inspired the reorganization of health services. Universities are training centers for professionals. The consequence of all this was the new challenges. Objective: The purpose of this study is to evaluate the compatibility between the objective of the teaching practice directed towards the SUS and the students' learning and understanding regarding preparation for Care Management in the SUS. It is an observational, exploratory, descriptive and inferential investigative process, using a qualitative approach. In this type of study, the following phases were covered: first, bibliographic survey of the study, to support the elaboration and application of three questionnaires and the construction of a semi-structured interview. Materials and Methods: A semi-structured questionnaire was applied to teachers and students in a hierarchical way for Bardin's content analysis, later the questionnaire was processed in the Iramutec software forming a cloud of words. When performing the semi-structured interview, it was observed that the predominance of traditional teaching, focused on lectures and qualitative assessments, such responses pointed to the identification of a traditional approach. Final Considerations: Educational practice is predominantly traditional and dichotomous, consisting of lectures that must be improved in order to train critical, reflective nurses capable of making decisions.